Endodontic Diagnosis, Pathology, and Treatment Planning Mastering Clinical Practice - Patel, Bobby. (Springer International Publishing : Imprint: Springer, 2015)
This book is intended as a practical guide to endodontic diagnosis, pathology, and treatment planning that avoids the pitfall of excessive theoretical information, common to many traditional endodontic textbooks. The coverage is comprehensive and encompasses such topics as disease classification, the endodontic armamentarium, anatomy, the role of different radiographic techniques, treatment decision making, preoperative management, the use of antibiotics and analgesics, and anesthesia. Numerous high-quality illustrations and clinical photographs are included to highlight key concepts and findings, and best practice is documented by means of clinical case examples. The provision of concise tips and recommendations ensures that the reader will quickly be able to find solutions to diverse endodontic challenges. In addition, the most relevant literature is reviewed in order to support and reinforce the discussed clinical concepts. The book will assist dental practitioners and endodontic trainees/specialists in planning the management of any endodontic case from first principles.